Task-board task for assembling a belt drive unit. (17th April 2020) - Shibata, Mizuho; Dobashi, Hiroki; Uemura, Wataru; Kotosaka, Shinya; Aiyama, Yasumichi; Sakaguchi, Takeshi; Kawai, Yoshihiro; Noda, Akio; Yokoi, Kazuhito; Yokokohji, Yasuyoshi
ABSTRACT: A task board is a board for assembling parts, developed to test the abilities of a robot system to perform assembly operations associated with a manufacturing process. This study describes a task board that can serve as a basis for developing program modules for assembling a specific product. A properly designed task board can serve as a preliminary template for a specific assembly and can promote robotic assembly. This study analyzes the design of a Task-board task performed at the World Robot Summit 2018 (WRS 2018). The main competitive task at the WRS 2018 was the assembly of a belt drive unit. Analyses showed that the directions of assembly, especially the horizontal direction, were common difficulties in both Task-board and Assembly task competitions. Development of a task board for a specific assembly product requires an increase of its relevance to the assembly product, such as using the same workpieces or using similar assembly orientations. GRAPHICAL ABSTRACT: